Understanding the synergistic catalytic effect between la2O 3 and CaO for the CH4 Lean De-NOx reaction: Kinetic and mechanistic studies - Anastasiadou, T.; Loukatzikou, Loukia A.; Costa, Costas (My University, 2005)
Doping of La2O3 crystallites with Ca2+ ions significantly enhances the intrinsic rate of NO reduction by CH4 in the presence of 5% O2 at 550°C compared to pure La 2O3 and CaO solids, while the opposite is true after doping of CaO with La3+ ions. It was found that the 5 wt % La 2O3-95 wt % CaO system has one of the highest intrinsic site reactivities (TOF = 8.5 × 10-3 s-1) reported at 550°C for the NO/CH4/O2 reaction among metal oxide surfaces. The doping process occurred after first dispersing La 2O3 and CaO crystallites in deionized water heated to 60°C for 90 min, while the dried material was then ground and heated slowly in air to 800°C and kept at this temperature for 5 h. The doping process had the effect of creating surface oxygen vacant sites (F-type defects) in the oxide lattices the concentration of which is a function of the wt % La 2O3 used in the mixed oxide system as revealed by photoluminescence and O2 chemisorption studies. According to DRIFTS 15NO transient isotopic experiments (SSITKA), oxygen vacant sites in Ca2+-doped La2O3 promote the formation of a more active chemisorbed NOx species (NO2 -) that contributes to the enhancement of reaction rate as compared to pure lanthana, calcium oxide, and La3+-doped CaO. These results were supported by the kinetic orders of the reaction with respect to NO and O2 obtained as a function of wt % La2O3 content in the mixed oxide system. Carbon dioxide (a reaction product) competes for the same oxygen vacant sites to form stable adsorbed carbonate-like species, thus lowering the reduction rate of NO. The dependence of the reaction TOF on the wt % La 2O3 loading at 550°C was found to follow the trend of the dependence of photoluminescence intensity on the wt % La2O 3 content in the La2O3-CaO oxide system.
Keywords: Calcium compounds; Chemisorption; Cyanides; Doping (additives); Lanthanum compounds; Photoluminescence; Reaction kinetics